2021
DOI: 10.3390/nu13010266
|View full text |Cite
|
Sign up to set email alerts
|

Eat Your Broccoli: Oxidative Stress, NRF2, and Sulforaphane in Chronic Kidney Disease

Abstract: The mainstay of therapy for chronic kidney disease is control of blood pressure and proteinuria through the use of angiotensin-converting enzyme inhibitors (ACE-Is) or angiotensin receptor blockers (ARBs) that were introduced more than 20 years ago. Yet, many chronic kidney disease (CKD) patients still progress to end-stage kidney disease—the ultimate in failed prevention. While increased oxidative stress is a major molecular underpinning of CKD progression, no treatment modality specifically targeting oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 140 publications
0
24
0
Order By: Relevance
“…Therefore, the activation of Nrf2 has been related to the decrease in ROS overproduction, conferring protection against renal damage [ 19 , 28 ]. The Nrf2-activation-induced renal protection is promoted by using agents or molecules that enhance Nrf2 activity [ 25 , 29 ]. For instance, sulforaphane (SFN), an isothiocyanate derived from cruciferous green vegetables, has been shown to activate Nrf2 by reversibly modifying Keap1 cysteine residues [ 30 ].…”
Section: Preclinical Data Of Salutary Ambiguous or Disadvantageous Ef...mentioning
confidence: 99%
“…Therefore, the activation of Nrf2 has been related to the decrease in ROS overproduction, conferring protection against renal damage [ 19 , 28 ]. The Nrf2-activation-induced renal protection is promoted by using agents or molecules that enhance Nrf2 activity [ 25 , 29 ]. For instance, sulforaphane (SFN), an isothiocyanate derived from cruciferous green vegetables, has been shown to activate Nrf2 by reversibly modifying Keap1 cysteine residues [ 30 ].…”
Section: Preclinical Data Of Salutary Ambiguous or Disadvantageous Ef...mentioning
confidence: 99%
“…SFN is well established as one of the most important bioactive components of broccoli (Brassica oleracea var. Italica) and other cruciferous vegetables [38][39][40][41]. SFN is an isothiocyanate generated by the hydrolysis of glucosinolate glucoraphanin by myrosinase (this enzyme is present in plants and gastrointestinal microflora) [42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…However, the conformational alterations of KEAP1, due to the oxidation of some of its cysteine residues, prevent the degradation of NRF2, leading to its nuclear translocation and action upon gene expression [31,34]. Studies in human and animal models of different diseases such as cancer, cardiac pathologies, kidney disorders, diabetes or obesity have revealed a protective effect of the positive regulation of NRF2 in reducing the severity of the disease [35,36]. Interestingly, it has been demonstrated that consuming a diet rich in cruciferous vegetables can affect the KEAP1-NRF2 pathway [37].…”
Section: Health and Health Benefits Are Human Inventionsmentioning
confidence: 99%